UJI DAYA HAMBAT EKSTRAK BUAH TIN (Ficus racemosa Linn) TERHADAP PERTUMBUHAN Staphylococcus aureus ATCC 25923 - Ramadhan, Muhammad Rizal; Pratiwi, I Desak Putu Kartika; Hapsari A., Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
This research aims to test the inhibitory extract of fig fruit ( Ficus racemose Linn) by using aquadest solvent towards the growth of Staphylococcus aureus ATCC 25923. This research used an Completely Randomized Design with 5 concentrations level of fig fruit extract which were 20%, 40%, 60%, 80%, and 100% with three replications. The observed variable was quantitative test of total colony after contacted with fig fruit extract and calculate the percentage death of Staphylocccus aureus ATCC 25923 after contact. Data of this research was analyzed with analysis of variance and then continued with Duncan test. The result showed that the extract of fig fruit had a significant effect on inhibitory the growth of Staphylcccus aureus ATCC 25923 or has a bacteriostatic character with percentage range death of Staphylococcus aureus ATCC 2593 is 7.20% - 51.40%. Keywords : fig fruit, Staphylococcus aureus, antibacterial